Political Actor or Policy Instrument? Governance Challenges in Australian Local Government - Nicola Brackertz (Commonwealth Journal of Local Governance, 2013)
This article examines the governance challenges facing Australian local government, which include lack of constitutional standing, intergovernmental dependencies, financial constraints and weak democratic standing. The historical context has shaped the nature and place of local government in the Australian federal polity and has contributed to the tensions created by an expansion of the roles and responsibilities of local government, especially in the provision of services, which is not matched by concomitant increases in financial capacity and local autonomy. These governance challenges are discussed with a view to establishing local government’s capacity for autonomous self-governance in the face of intergovernmental and fiscal dependencies, and the implications of this for local government reform trajectories.